Improved Supervision of Loading and Unloading of Oil Fuel to Minimize Shrinkage of Loads at MT. Nirbita - Fuadaturrahmah Fuadaturrahmah; Marsel Arinaek Manurung (Institute of Computer Science (IOCS), 2020)
This study aims to determine the importance of monitoring loading and unloading of fuel oil to minimize the occurrence of load shrinkage. After conducting an evaluation of existing events, two main problems were found that occurred in the implementation of ISGOTT in MT. Nirbita, namely the problem of lack of supervision and accuracy of loading and unloading fuel oil resulting in load shrinkage. The occurrence of cargo depreciation on board the ship is a lack of proper supervision according to ISGOTT by Officer Deck for Abk during cargo operations. The occurrence of cargo losses is also due to the lack of accuracy of deck and abk officers in measuring cargo tanks and calculating cargo as well as standardization of loading and unloading equipment onboard resulting in less optimal operational cargo. Lack of understanding of matters relating to cargo operations, both those related to measuring instruments used on tanker ships, triggers cargo depreciation. There are three alternative solutions to problems, namely conducting safety meetings, conducting training, and supervising Abk's work in cargo operations. From the results of the evaluation of the three alternative solutions to the problem, it was found that each alternative has advantages and obstacles that will be faced in its application on board.